Analisis Kewenangan Pemerintah Terkait Pembangunan Flyover di Jalan Wiratno Terhadap Asas Good Governance - Muhammad Rayhan Nova Ramadhan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the government's authority regarding the construction of the Jalan Wiratno Flyover in Tanjungpinang City, viewed through the lens of Good Governance principles. The flyover project is a local government initiative designed to enhance transport connectivity, facilitate the smooth mobility of the public, and support the development of urban areas and the government administrative hub in the Riau Islands Province. This study employs a qualitative research method. Data were gathered through interviews with relevant government agencies and affected community members, and supplemented by a review of legislation and documents related to infrastructure development. The findings indicate that the government carried out the construction based on the authority granted by Law Number 23 of 2014 concerning Regional Government and adhered to the applicable planning, budgeting, and implementation mechanisms. Regarding Good Governance, the government endeavored to uphold transparency, accountability, and public participation through regional development planning mechanisms. However, the study reveals areas requiring optimization specifically in improving public communication, information dissemination, and the engagement of directly affected communities to ensure a comprehensive understanding of the project's objectives. Furthermore, the compensation mechanisms for affected residents need to be continuously refined to ensure fairness and compliance with statutory regulations. In conclusion, the government's exercise of authority in the Jalan Wiratno Flyover project aligns with prevailing legal provisions; meanwhile, the continued optimization of Good Governance principles is expected to enhance infrastructure development effectiveness, deliver broader public benefits, and strengthen the quality of local governance.